1998
DOI: 10.1023/a:1008418727472
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral T-cell lymphomas: Initial features, natural history, and prognostic factors in a series of 174 patients diagnosed according to the R.E.A.L. Classification

Abstract: PTCL have adverse prognostic features at diagnosis, respond poorly to therapy and have short survival, with no sustained remission. ALCL constitutes a subgroup which responds better to therapy and has a longer survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
202
2
7

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(238 citation statements)
references
References 34 publications
19
202
2
7
Order By: Relevance
“…This finding was consistent with earlier reports in which CR rates for PTCLs ranged from 31% to 69%. 2,6,7,9,15,16 Furthermore, in the pre-rituximab era, the long-term remission rate was 50-60%, which is consistent with our result. If rituximab were combined with the CHOP regimen for CD20-positive DLBCL, the difference in CR rates between PTCLs and DLBCL would be expected to increase, as most studies have suggested that primary regimens containing rituximab improved the CR rate and long-term outcomes of DLBCL patients.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This finding was consistent with earlier reports in which CR rates for PTCLs ranged from 31% to 69%. 2,6,7,9,15,16 Furthermore, in the pre-rituximab era, the long-term remission rate was 50-60%, which is consistent with our result. If rituximab were combined with the CHOP regimen for CD20-positive DLBCL, the difference in CR rates between PTCLs and DLBCL would be expected to increase, as most studies have suggested that primary regimens containing rituximab improved the CR rate and long-term outcomes of DLBCL patients.…”
Section: Discussionsupporting
confidence: 92%
“…15,16 In Western countries, by contrast, high-risk groups account for only 42-46% of patients with PTCL. 2,9,17 Although the IPI for PTCLs appears to be higher in Japan than in Western countries, international studies with large patient populations will be required to confirm the racial differences in the clinical characteristics of PTCLs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the clinical outcome is poor with this therapy except for anaplastic large-cell lymphoma (ALCL), ALK positive type [2]. Large prospective series did indicate a higher relapse rate and a poorer survival for PTCL than DLBCL [2,[5][6][7][8][9][10][11][12][13]. Various chemotherapy regimens have been tried out--such as MegaCHOP (intensive or higher dose of CHOP) with or without etoposide [14,15], epirubicin substituted for doxorubicin and addition of bleomycin (CEOP-B) [16], CMED (cyclophosphamide, etoposide, methotrexate, and dexamethasone) [17], CHOP or MegaCHOP/ESHAP (etoposide, cisplatin, cytarabine and prednisone) [18,19] and VCAP-AMP-VECP (vincristine, cyclophosphamide, doxorubicin, and prednisone (VCAP); doxorubicin, ranimustine, and prednisone (AMP); vindesine, etoposide, carboplatin, and prednisone (VECP)) [20]; fractionated cyclophosphamide, vincristine, doxorubicin and dexamethasone alternating with high doses of methotrexate and cytarabine (hyperCVAD) [21,22]--with no superior efficacy to CHOP except CMED at the expense of higher treatment toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…2 Retrospective analyses using WHO criteria have generally found a worse outcome for PTCL (long-term overall survival (OS) 26-41%) than that seen for B-cell lymphoma following conventional chemotherapy, especially if anaplastic large-cell lymphoma (ALCL), a good prognosis subtype of PTCL, is excluded. 1,[3][4][5][6] The favorable outcome of ALCL (60% OS at 5 years after standard therapy) is associated with the expression of anaplastic lymphoma kinase (ALK), seen in half of the cases. 4,5,7,8 In general, the initial chemosensitivity but poor ultimate outcome of PTCL has fueled interest in high-dose therapy and autologous stem cell transplantation (ASCT) as a means to improve cure rates.…”
Section: Introductionmentioning
confidence: 99%